Withdrawal of distal embolism protection device İn extreme case of tortuous carotid - (:unkn) unknown (My University, 2022)
An 81-year-old male with a history of left-sided hemiplegia was referred to our outpatient clinic when his computed tomography (CT) angiography indicated %99 stenosis in the left internal carotid artery (ICA). He had also a history of CABG( 10 years ago) and diabetes mellitus. The patient was consulted to our department of neurology and cardiovascular surgery for possible intervention to the left ICA. Carotid artery stenting was considered a more suitable approach for this patient rather than endarterectomy. Carotid angiography demonstrated %80 stenosis in the left ICA. Procedure: 7F sheathless catheter was advanced into the left common carotid artery. The lesion was crossed using 0.014 wire (Floppy). After placement of distal embolic protection device (Spider) to distal ICA, 6x30 mm self-expandable stent did not pass through to the lesion due to severe tortuosity and then extra support floppy wire used as body wire after that stent located properly and body wire pull back stent implanted. Post dilatation did with a 5x20 semi-compliant balloon. During the withdrawal of the distal embolic protection device, it was seen that the device was attached to the stent distal strata and therefore could not be withdrawn. The patient's stent was manipulated from the outside to the neck area by hand so that the device could be successfully withdrawn. Control angiography revealed no rupture or any other complication after the procedure.
Keywords: Tıp; Sağlık Bilimleri; Medicine; Health Sciences; Klinik Tıp (MED); Klinik Tıp; Clinical Medicine (MED); CLINICAL MEDICINE; Carotid artery; EPD; Stenting